Effects of increasing levels of rubber seed cake on growth performance, nutrient digestion metabolism, serum biochemical parameters, and rumen microbiota of Hu sheep - Huwei Zhao; Jinling Hua; Wenwen Lu; Longfei Yan; Min Zhang; Chao Chen; Xiaokang Lv (BMC Veterinary Research)
Abstract This study aimed to reveal the effects of increasing levels of rubber seed cake (RSC) on growth performance, nutrient digestion metabolism, serum biochemical parameters, and rumen microbiota in Hu sheep. In this study, 48 Hu sheep, weighing 17.01 ± 0.57 kg at 3 months of age, were randomly divided into four treatments: 0% rubber seed cake (RSC0%), 6% rubber seed cake (RSC6%), 12% rubber seed cake (RSC12%) and 18% rubber seed cake (RSC18%), with 12 sheep per group. Compared to the RSC0%, the ADG and DMI of the RSC6% and RSC12% were increased (P > 0.05). The apparent digestibility of OM and EE quadratically (P < 0.05) changed with the increase of RSC supplementation, with the greatest apparent digestibility of OM and EE observed in the RSC6% diet. With increased RSC supplementation, the N intake and fecal N increased linearly (P < 0.05), and the apparent digestibility of N reduced linearly (P < 0.05). As the increase of RSC supplementation, the serum levels of IgA, IgM, IgG, IL-4, T-AOC, and GSH-Px increased linearly (P < 0.05), and the serum level of IL-6 reduced linearly (P < 0.05). The serum level of IL-1β reduced quadratically (P < 0.05) with the increased RSC dose, and the serum level of SOD increased quadratically (P < 0.05) with the increased RSC dose. The ruminal NH3-N and the relative abundance of norank_Muribaculaceae quadratically (P < 0.05) changed with increased RSC supplementation, and the greatest relative abundance of norank_Muribaculaceae was observed in the RSC6% diet. In general, incorporating RSC into the diet of Hu sheep did not adversely affect growth performance and rumen fermentation characteristics. Supplementing with 6% RSC enhanced the relative abundance of norank_Muribaculacea in the rumen fluid and the immune and antioxidant capabilities. However, supplementing with 12 and 18% RSC might have negatively impacted nutrient digestion and metabolism. Therefore, this study recommended replacing corn and soybean meal with 6% RSC in the diet of Hu sheep.